Pesticidal Activity of Leaves and Seeds Extracts of Tephrosia vogelii Hook. f. and Ricinus communis L. on Insects Damaging Crops and Stored Food - Nizigiyimana, Liberata; Ngendakuriyo, Alexis; Ngezahayo, Jeremie; Nihorimbere, Manasse; Katihabwa, Aloys; Nduwarugira, Deogratias (European Scientific Journal, ESJ, 2026)
Biopesticides, rather than synthetic pesticides, are more highly recommended for insect pests control because they are environmentally friendly and safe for human health. This study aimed to highlight the pesticidal effect of Tephrosia vogelii and Ricinus communis on four insects: Spodoptera frugiperda, Aphis fabae, Acanthoscelides obtectus, and Sitophilus zeamais. The leaves and seeds of these plants were collected from the fields, dried and powdered. An amount of powder was macerated and the extracts were used to perform phytochemical screening and test their toxicity to these insects in field and in laboratory. Results showed that the phytochemistry of the two plants varied from one plant to another and from one extract to another. Aqueous extracts of fresh T. vogelii and R. communis leaves (125g/l and 250g/l, respectively) resulted in mortality rates exceeding 50% for A. fabae. Aqueous extracts of T. vogelii leaves were more effective than those of R. communis leaves against S. frugiperda in terms of mortality rates. LD50 of aqueous extracts of T. vogelii leaves was 114g/l for A. fabae. Most organic extracts (4mg/ml) of both plants achieved mortality rates exceeding 60% for A. obtectus and S. zeamais. Hexane extract (4mg/ml) of T. vogelii leaves and seeds showed better results for treating A. obtectus (LD50 = 1 mg/ml–1.33mg/ml). Similarly, hexane extract of T. vogelii seeds showed better results for treating S. zeamais (LD50=1.66mg/ml). Therefore, it can be concluded that R. communis and T. vogelii could be alternative treatments for insect pests of crops and harvests.